Don Tillman's Hierarchy of Needs in Graeme Simsion's The Rosie Project - Oki Maulina Diakita; Tri Pramesti (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2023)
Abstract. In this research, the writer discusses and analyzes the hierarchy of human needs of Don Tillman in a novel entitled The Rosie Project by Graeme Simsion. Don Tillman, the main character may have a perfect life but he has a trouble to fit in socially. This study uses the theory of the hierarchy of needs of Abraham Maslow. This research uses a qualitative descriptive method. The data source used for the research is taken from the novel. Data collection is done by reading the novel, marking the data, grouping the data, and selecting the data. To analyze the data is done by analyzing and describing the data presented. This research shows that Don Tillman has fulfilled his five needs starting from physiological needs, safety, love and belonging, appreciation, and self-actualization. Even though there are obstacles in meeting these needs, especially the need for security and the need for love and belonging, Don Tillman is able to overcome them and successfully fulfill these needs.